1990
DOI: 10.1002/bit.260350914
|View full text |Cite
|
Sign up to set email alerts
|

Biological removal of toxic chromium using an Enterobacter cloacae strain that reduces chromate under anaerobic conditions

Abstract: Hexavalent chromium (chromate: CrO.+-) is toxic and mutagenic for most organisms.'.* In humans, chromate causes irritation and corrosion of skin and respiratory tract, and is believed to be responsible for lung carcinoma. Chromate is also hazardous to fauna and flora in natural aquatic ecosyst e m~.~ Wastewaters containing toxic chromate are generated in many industrial processes including chrome leather tanning, chromium plating, metal cleaning and processing, wood preservation, and alloy p r e p a r a t i~n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 5 publications
0
18
0
4
Order By: Relevance
“…These findings reinforce the need to identify important electricity-generating bacteria in MFCs by using techniques that isolate bacteria based on their ability to generate current and not just their dissimilatory iron reduction ability. Although E. cloacae could not reduce Fe(III), it has been reported that this strain can reduce soluble chromate ion to Cr(III) and selenate to selenium (16,17).…”
Section: Discussionmentioning
confidence: 90%
“…These findings reinforce the need to identify important electricity-generating bacteria in MFCs by using techniques that isolate bacteria based on their ability to generate current and not just their dissimilatory iron reduction ability. Although E. cloacae could not reduce Fe(III), it has been reported that this strain can reduce soluble chromate ion to Cr(III) and selenate to selenium (16,17).…”
Section: Discussionmentioning
confidence: 90%
“…Philip et al [50] reported that the presence of up to 1,000 mg/L (10.4 mM) of sulfate did not affect Cr(VI) reduction by Bacillus coagulans. However, Cr(VI) reduction by Enterobacter cloacae HO1 under anaerobic conditions showed 32% inhibition in the presence of only 25 lM of sulfate [26].…”
Section: Resultsmentioning
confidence: 97%
“…that reduce Cr(VI) are P. ambigua C-13 and P.¯uorescens LB300, the latter aerobically and anaerobically (Bopp and Ehrlich, 1988). Among enterobacterial strains, Enterobacter aerogenes EAO reduced Cr(VI) in rich medium, with chromate reductase activity induced by nitrite (Clark, 1994), whereas E. cloacae HO1 reduced up to 2 mM CrO 4 2) to Cr(III), which was precipitated in the culture medium as Cr(OH) 3 anaerobically (Komori et al, 1990) at pH 7.0 to 7.8 (De Mel et al, 1994). In contrast, Escherichia coli ATCC 33456 reduced Cr(VI) aerobically and anaerobically within 12 h (Shen and Wang, 1993), but the product of the reaction [probably Cr(III)] was almost completely (98%) retained in a soluble form in the culture supernatant (Shen and Wang, 1993).…”
Section: Introductionmentioning
confidence: 98%